Diseño del Acceso Principal a las Labores de Exploración y Explotación Presentes en la Mina “El Faique” codigo:485, Sector Laguar, Cantón Macará, Provincia de Loja. - Valle Maza, Félix Alejandro (2024)
This research was developed with the purpose of establishing the main access to the exploration and exploitation works in the “El Faique” mine, code 485, located in the province of Loja, Macará canton, Laguar sector. The research began with the collection of bibliographic, cartographic and geological information, after which work was carried out in a field, laboratory and office phase. The field phase consisted of topographic survey, sample collection, rock identification and characterization of the rock mass to prepare topographic, lithological and geomechanical maps that serve as a basis to meet the objective of locating the most appropriate places to build the mine access. In the laboratory phase, the analysis of the physical and mechanical properties was carried out. Within the physical properties, the following were determined: apparent specific weight, real specific weight, moisture content and porosity. For the mechanical properties, the resistance to simple compression was determined, in which samples of the rock mass were taken and tested with the hydraulic press. In the office phase, the interpretation of results was preceded by obtaining lithologies of the study area, calculation of the physical and mechanical properties and in turn the geomechanical classification of the rock mass was also carried out using Bieniawski's RMR and Barton's Q index. With this information as a basis, each of the proposed alternatives was analyzed. Initially, four access points were identified where the mineralized zone could be reached, however, through assessment matrices and criteria, it was determined that the most appropriate alternative is the fourth, which deals with an inclined plane of 23º. Once the type of access was determined, the excavation design was carried out, in which dimensions of 2.70 m wide and 2.80 m high were established, and from there the construction process of the mining work was developed, determining the excavation method, excavation equipment, ventilation, drainage, lighting, work cycle diagram and costs. Finally, a benefit ratio was established on the construction of the access. Keywords: Physical properties, geomechanical properties, morphology, igneous rocks, geology.